Symptomatic tension pneumocephalus following Palacos® cranioplasty in a shunted patient. (4th March 2019) - Killeen, Tim; Fortunati, Mathias; Myanger, Esha; Rüfenacht, Daniel; Ryskeldiyev, Nurzhan; Akshulakov, Serik; Cesnulis, Evaldas
Abstract: Tension pneumocephalus is an exceedingly rare complication of cerebrospinal fluid diversion occurring after surgery, trauma or spontaneous fistula formation. We report a case in a patient with a ventriculoperitoneal shunt who developed symptomatic tension pneumocephalus via a skin defect within 24 hours of undergoing bone cement cranioplasty.